Peran Katekis dalam Membimbing Generasi MudaMenghadapi Tantangan Zaman Berdasarkan Dokumen Antiquum Ministerium - Monica Innanda Chiaralazzo; Alfonsus Krismiyanto (Sekolah Tinggi Agama Katolik Negeri Pontianak, 2025)
Young people face complex challenges of the times, including secularism and individualism. Both of these beliefs can lead to young people losing fundamental religious and moral values. This research employs a literature study method by examining the document Antiquum Ministerium to explore the role of catechists in assisting young people in facing the challenges of the times.The study found that catechists play an important role in helping young people understand and integrate religious values into their daily lives. How ever, catechists also face challenges in proclaiming the Gospel to young people. Young people today have the freedom to make their own choices in life, including in matters of religion. Therefore, catechists need to be open and respect the beliefs and choices of young people. To overcome these challenges, catechists need to have adequate knowledge and skills in proclamation and pastoral care. They also need to use communication media that are relevant to the needs and interests of young people. With these efforts, it is hoped that catechists can be agents of change in helping young people to become people of faith, morality, and responsibility.